Preliminary results of progenies testing of the best and normal trees of Douglas fir (Pseudotsuga menziesii (Mirb.) Franco) in the Forest-Steppe in Ukraine - Plotnikova , O. M. (Forestry and Forest Melioration, 2020)
Introduction The introduction of Douglas fir (Pseudotsuga Menziesii (Mirb.) Franco) into the forests in Forest-Steppe is constrained by the poorly developed forest seed base. Therefore, it is advisable to select plus trees, establish objects of a permanent forest seed base on their basis and test progenіes of the best Douglas fir trees. For this purpose, a complex assessment of the progenіes of the best and normal Douglas fir trees was carried out to determine promising ones for harvesting seeds and cuttings and to further use them when creating seed orchards in Ukrainian Forest-Steppe. Materials and Methods The study determined heights and root system lengths of 2-year-old seedlings of Douglas-fir in the greenhouse of Guty Forest Enterprise, grown from seeds harvested from the best and normal trees in the experimental plantation of Kharkiv Forest Research Station in Kharkiv Region. The seedling seed orchard of Douglas fir was created in Vinnitsa Forest Research Station in Vinnytsia Region, and it has 17 progenies. The progenies were observed at the age of 3, 6 and 8. A complex assessment was carried out on a scale using equivalent indicators: growth intensity, condition, stem straightness. Results The average height of the aboveground part of 2-year-old seedlings ranged from 20.6 (progeny 2-11) to 33.5 cm (progeny 1-6), the average length of the root system – from 16.1 (progeny 2-11) to 25.0 cm (progeny 5-19) and were characterized by a low level of variability between variants. The studies of the progenіes of the best and normal Douglas-fir trees on seedling seed orchard in the Right-Bank Forest-Steppe of Ukraine revealed differentiation of growth dynamics in height over 8 years. Plants of progeny 1-6 had the most average heights during the entire observation period, progenіes 5-19 and 11-18 – from 6-year-old. At the age of 8, families 1-5, 1-6, and 5-19 were characterized by the highest values of the root collar diameter, family 2-11 – by the lowest ones. Preservation of Douglas fir progenіes on the plantations in 2019 averaged 61.5%. The condition of the trees was good. The part of trees with straight stems was 42.9% or more. A complex assessment of the growth, condition and stems straightness of the progenіes of the best and normal Douglas fir trees showed that five trees (1-5, 1-6, 3-16, 5-19, 11-18) growing in the experimental plantations of Kharkiv Forest Research Station, can be previously recommended for the harvesting seeds and cuttings for the establishment of seed orchards in the Forest-Steppe conditions of Ukraine. The other 10 trees require a further investigation based on the research of their progenіes. It is recommended to use the seeds of all evaluated best and normal trees (seed mixture) to establish permanent forest seed stands. Conclusions Taking into account biological peculiarities of Douglas fir which is characterized by moderate growth up to 10 years, studies in older age will allow us to more precisely interpret the obtained test results of the best and normal Douglas fir tree progenies and determine the beginning of the period of intensive tree growth in Forest-Steppe. According to the preliminary results of the complex assessment, it is planned to include the best Douglas fir trees – candidates for plus trees, selected in the experimental plantation of Kharkiv Forest Research Station, in the State Register of plus trees. 6 Figs., 4 Tables, 26 Refs. Key words: Pseudotsuga Menziesii, progeny, seedling seed orchard, stem straightness, complex assessment.